Syrian Families in Germany - Kaidouha, Kutaiba (Nomos Verlagsgesellschaft mbH & Co. KG, 2025)
This book highlights the dynamics and conflicts of Syrian families within the German asylum context; examining the interplay of cultural; social; economic; and legal factors shaping familial relationships. Using anthropological methods such as participant observation; interviews; and focus groups; the book analyzes the challenges faced by Syrian families before; during; and after displacement. It focuses on marital conflicts influenced by gender roles; economic changes; cultural and religious differences; and the legal frameworks in Germany. Finally; it explores conflict resolution strategies within the new social and legal environment. This book provides readers with a profound understanding of the challenges and adaptations of Syrian families in the asylum context.